Adults Learners' Perception on English Communication Skills for Civil Servants Online Training - Wahyu Pramudita; Anastasia Sastrikirana (Universitas Cokroaminoto Palopo, 2022)
Abstract Since 2019, the Language Training Center of the National Institute of Public Administration (NIPA) has conducted English online training. However, when the Covid-19 was announced pandemic, the way it was organised had to be adjusted. Organising online learning is a way that enables the learning process to continue. The classical interaction turns into virtual interaction using online learning platforms. Although there are many barriers in organising an online learning environment, it still has to be carried out since it is one of the responsibilities of the Language Training Center of NIPA. There are a lot of aspects to consider in organising English online training, one of which is interaction. Interaction takes most of the successful learning indicators: interaction between tutors and participants and among participants. In regards to this current situation, this study would like to analyze the participants’ perception on the English online training. There were 40 participants of English Communication Skills for the Civil Service (ECSCS) Training. The research data was obtained from the questionnaire whose content covered three aspects, which include learning materials, atmosphere or classroom environment, and interactions. Participants responded to a questionnaire about the English online training that they experienced in the midst of the Covid-19 pandemic. The results of the data indicated that to a great extent, the participants agree that the learning materials, the atmosphere or learning environment, and the interaction during the English online training made them more motivated in learning English and able to apply English in context.